Effect of Progressive Muscle Relaxation on Blood Pressure and Sexual Quality of Life in Hypertensive Patients - Faradilla Miftah Suranata; Cut Mutiya Bunsal; Helly M. Katuuk (Science Midwifery, 2022)
Increased blood pressure and decreased quality of sexual life are often found in patients with hypertension. Hypertension that occurs in the long term and continuously can trigger strokes, heart attacks, heart failure, and is the main cause of chronic kidney failure. The effect of Progressive Muscle Relaxation is a relaxation technique and non-pharmacological therapy that can lower blood pressure and improve the quality of sexual life in hypertensive patients. The purpose of this study was to determine "Progressive Muscle Relaxation on Blood Pressure and Quality of Sexual Life in Hypertensive Patients". The research method is pre-experimental design with a one-group pretest-posttest design. The sample of respondents in this study were 15 people with Accidental Sampling sampling technique. Collecting data using observation sheets and questionnaires. Analyzed by statistical test Paired t-test and Wilcoxon. The results of statistical tests on the average systolic blood pressure 137.60 mmHg and the average diastolic blood pressure 81.40 mmHg before being given therapy with a p-value of 0.001; the average systolic blood pressure was 123.93 mmHg and the average diastolic blood pressure was 76.47 mmHg after being given therapy with a p-value of 0.000; the average quality of sexual life for men was 74 and the average quality of sexual life for women was 42.80 before being given therapy with a p-value of 0.225; the average quality of sexual life for men is 77 and the average quality of sexual life for women is 49.40 after being given therapy with a p-value of 0.135.